Coupling Effects of Microstructure Characteristics on Stress Distribution for Pore-Scale Gas Diffusion Layers - Yushuai Sun; Pinliang Du; Miaoqi Bian; He Miao; Hao Hu; Liusheng Xiao (Energies)
A gas diffusion layer (GDL) is an essential component for the efficient operation of proton exchange membrane fuel cells, requiring stable mechanical strength and uniform stress distribution to achieve higher durability. The various microstructure characteristics of GDLs have coupled and complex effects on mechanical properties, which have not been fully considered in previous studies. In this study, we have combined stochastic reconstruction techniques, explicit dynamics compression simulation, and orthogonal design methods to evaluate and optimize the coupling effects of carbon fiber diameter, porosity, GDL thickness, and fiber orientation coefficient on the mechanical properties of pore-scale GDLs. Finally, mathematical expressions have been developed to predict stress distribution under compression. The results show that the impact of fiber diameter and porosity is greater than that of GDL thickness and fiber orientation coefficient. Average stress and stress uniformity increase with increases in fiber diameter, fiber orientation coefficient, and GDL thickness, but porosity shows an opposite trend. We achieved a remarkable reduction of 292% in optimal average stress and a significant enhancement of 278% in stress uniformity. The mathematical expressions have been validated for accuracy by considering the simultaneous coupled effects of various microstructural characteristics. This work provides valuable engineering tools for enhancing the performance and durability of GDLs and fuel cells.